RELIGIOSITAS TRADISI JAWA ISLAM DALAM SENI BATIK - Naomi Kawasaki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
This paper discusses the contents of religious values in batik. Classicalbatik motifs interpreted as decoration that was created in ancienttimes. The ornament is not something that only visually beautiful, butalso given a meaning that is closely related to Javanese philosophy ofhuman life. This means that the Java man, the beauty of decorative batikis more understood as an attempt to provide breath and soul of traditionalclothing. In the life cycle of Java people, Solo batik cloth used in theevent-related customs Javanese ritual called slametan (salvation). Slametanceremony is a socio-religious activities of the Java community.